THE OBJECTIVE OF RESEARCH WAS TO FIND OUT THE EFFECTIVENESS OF JIGSAW MODEL DISCUSSION TECHNIQUE TO IMPROVE THE SELF-CONFIDENCE. THIS STUDY EMPLOYED AN EXPERIMENTAL RESEARCH DESIGN WITH NONEQUIVALENT CONTROL GROUP DESIGN. THE SUBJECT OF RESEARCH WAS THE V - Wiharani, Benty (Universitas Sebelas Maret, 2014)
The objective of research was to find out the effectiveness of jigsaw model discussion technique to improve the self-confidence.This study employed an experimental research design with Nonequivalent Control Group Design. The subject of research was the VII graders of SMP Negeri in Boyolali consisting of 60 students. The data source derived from primary data, collected using self-confidence scale instrument. The data analysis was conducted using Independent Sample T Test and Paired Sample T Test with SPSS Statistic 20 software help. The result of research showed that there was a very significant difference of self-confidence feeling between the experiment group receiving jigsaw model discussion technique treatment and the control group not receiving, with t statistic of 9.224 with p value of 0.000 < 0.05.Considering the result of research, it could be concluded that the jigsaw model discussion technique effectively improved the self-confidence.